1999
DOI: 10.1046/j.1365-2346.1999.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Light-guided tracheal intubation using a prototype illuminated flexible catheter through the intubating laryngeal mask

Abstract: We evaluated the efficacy of a newly developed prototype illuminated flexible catheter to facilitate tracheal intubation through the intubating laryngeal mask and compared this light-guided technique with the conventional blind tracheal intubation through the intubating laryngeal mask. The illuminated flexible catheter consists of a completely flexible thin plastic catheter, a bulb attached to its distal end, a 15-mm concentric adapter at its proximal end connected with a battery and a power switch. The device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…These results are in agreement with those reported in a similar randomised, double cross over comparative study [1], using a prototype flexible lightwand (FLW) [2]. However, Kihara et al .…”
supporting
confidence: 92%
“…These results are in agreement with those reported in a similar randomised, double cross over comparative study [1], using a prototype flexible lightwand (FLW) [2]. However, Kihara et al .…”
supporting
confidence: 92%
“…In the three patients with a down folded epiglottis, the visual control of the endotracheal tube tip helped to adapt the intubation procedure instantly, instead of blind probing for the laryngeal inlet. Therefore, the proposed endoscopic monitoring technique converts the primary blind intubation procedure into a safe and atraumatic intubation technique and carries advantages similar to those of an illuminated catheter, recently reported by Dimitrious and Voyagis [16]. This helps to prevent potential complications, such as oesophageal intubation or trauma to the upper airway [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…The light-guiding catheter was inserted through the oesophagus airway. The following manoeuvres were applied according to the location of the glow [19]. If the glow was above the laryngeal prominence and in the midline, but the light-guiding catheter could not be moved downward, it indicated that the ventilation hole of the oesophagus airway might be above the glottis.…”
Section: Methodsmentioning
confidence: 99%
“…We defined each light-guiding catheter insertion after oesophagus airway adjustment as an additional attempt. A bright glow in the midline at the level of the laryngeal prominence and the same disappearing at the level of the suprasternal notch indicated that the light-guiding catheter had passed the glottis and entered into the trachea [19]. Thereafter, the oesophagus airway was withdrawn and removed carefully with the light-guiding catheter still in the trachea.…”
Section: Methodsmentioning
confidence: 99%